Framing the Decision: An Experimental Study of Managerial Judgments after Leadership Training - Aksoy, Yasin; Mehmet Sahinkoc, Ender (European Scientific Journal, ESJ, 2025)
The present study aims to contribute to the interdisciplinary discourse within behavioural economics and managerial psychology by examining the role of cognitive biases in managerial decision-making. Specifically, it investigates the framing effect - an established cognitive heuristic - by exploring how identical market information presented in either a gain-oriented (positive) or loss-oriented (negative) frame influences managerial investment decisions differently. A fundamental objective of the present study is to examine the moderating effect of transformational leadership training in diminishing vulnerability to framing-induced distortions. A total of 45 managers employed by the university participated in the research study. All participants initially underwent a standardised four-hour training session focusing on the principles of transformational leadership. Participants were then randomly allocated to one of two experimental conditions. Each group was provided with investment scenarios of an identical nature, but with different informational framing: one emphasised potential gains (positive framing), while the other foregrounded potential risks and uncertainties (negative framing). Participants were then invited to respond to the following question: ’Should the company enter the market under these conditions?’, and to provide a concise written rationale to support their response. The present study employs a mixed-methods experimental design, integrating quantitative and qualitative analytical approaches. Quantitative analysis revealed no statistically significant differences in decision outcomes between framing conditions (χ² ≈ 0.045, p > 0.05). However, a subsequent qualitative content analysis of the open-ended justifications revealed that participants’ cognitive reasoning was markedly sensitive to the framing manipulation. The respondents who were exposed to positive framing predominantly employed opportunity-centric rationales, whereas those exposed to negative framing articulated risk-averse arguments. These findings are consistent with the theoretical propositions of prospect theory (Tversky & Kahneman, 1981) and the risk-as-feelings hypothesis (Loewenstein et al., 2001), both of which emphasise the interaction between cognitive heuristics and emotional responses in decision-making contexts. It is noteworthy that the absence of significant outcome variation may imply that transformational leadership training has mitigated the behavioural impact of framing. Thematic analysis suggests that there are nuanced shifts in cognitive processing and increased resilience to framing effects among trained participants. The study under discussion highlights the importance of cognitive framing in shaping managerial judgements and the potential of leadership-oriented cognitive interventions to mitigate such biases. The present study makes a novel contribution to the extant literature on behavioural decision-making, executive cognition and leadership development within organisational contexts.